Stereotactic Ablative Body Radiation Therapy for Spinal Oligometastases: Experience at a Single New Zealand Institution - Kathryn Tucker; Komeela Naidoo; Nur Azri Bin Mohd Yasin; John Chin; Charles De Groot; Roger Huang (Journal of Medical Imaging and Radiation Oncology, 2026)
ABSTRACT Purpose Spinal metastases are a common complication of advanced malignancy and can result in significant pain, neurological dysfunction, and reduced quality of life. In patients with oligometastatic disease, stereotactic ablative body radiation therapy (SABR) offers the potential for durable local control. This study reports outcomes following spinal SABR at Waikato Hospital and compares these with published literature. Methods A retrospective single‐centre cohort study was conducted of patients with oligometastatic spinal metastases treated with SABR at Waikato Hospital between September 2019 and December 2023. Patient, tumour, and treatment characteristics were collected from electronic records. The primary outcome was freedom from local failure. Overall survival and adverse events were also assessed. Results Twenty‐seven patients received 30 courses of spinal SABR. Median age was 66 years (range 37–81), 74.1% were male, and prostate cancer was the most common primary malignancy (48.1%). Metachronous oligorecurrent disease was present in 53.3% of patients. Patients received either 24 Gy in 2 fractions (60.0%) or 35 Gy in 5 fractions (40.0%). Median follow‐up was 29.7 months. No failures occurred within 12 months. Freedom from local progression was 95.2% (95% CI 86.6–100) at 18 months and 77.6% (95% CI 57.3–100) at 3 years. Overall survival was 88.9% (95% CI 77.8–100) at 1 year and 66.3% (95% CI 49.5–88.9) at 3 years. Vertebral compression fractures occurred in 13.8 % of treated sites. Conclusion This study provides important outcome data from a New Zealand tertiary centre and demonstrates the feasibility of spinal SABR, with outcomes which are broadly consistent with those reported internationally.